Validating a Model for Information Literacy Instruction for Elementary School Students: A Study - Nesset, Valerie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
A qualitative study was conducted with third-grade students to validate and ascertain the efficacy of an empirically-based model integrating features from research into information-seeking behavior and information literacy and specifically developed for information literacy instruction of younger elementary school students. Une étude qualitative a été menée auprès des élèves de troisième année dans le but de valider et de vérifier l'efficacité d'un modèle empirique intégrant des aspects de la recherche sur le comportement de recherche d'information et sur la compétence informationnelle, modèle développé spécifiquement pour l'enseignement des compétences informationnelles aux élèves les plus jeunes à l'école primaire.